(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Objectives: Thalassemia with frequent blood transfusion was considered under oxidative stress because of the chance of iron overload. Patients with thalassemia trait with no blood transfusion might also suffered from oxidative stress because of increased iron metabolism. This pilot study was to investigate if patients of alpha or beta thalassemia trait and received no blood transfusion were suffered from oxidative stress in term of DNA damage in peripheral leucocytes. Method: Comet assay was used to measure DNA damage of 20 normal subjects, 8 alpha and 12 beta thalassemia patients who did not received blood transfusion. The baseline and UV-mediated DNA damages of peripheral white blood cells were measured. The degree of DNA damage was quantified by visual scoring under light microscope after staining with Giemsa stain. Results: The mean (± standard deviation) comet score for normal baseline samples was 8.3 ± 6.1 whereas 105.4 ± 15.7 and 69.8 ± 20.3 for alpha and beta thalassemia respectively. While the comet scores were 71.9 ± 19.6, 193.1 ± 21.8 and 211.8 ± 51.6 for normal, alpha and beta thalassemia samples respectively in UV-treated samples. Results showed that both alpha and beta thalassemia patients had higher leucocytic DNA damage in baseline and oxidative stressed samples. Conclusion: Our data suggested thalassemia patients were under oxidative stress even no iron over loaded through transfusion.